Efeitos de 4 dias de sobrecarga de frutose sobre a reatividade vascular de ratos machos e fêmeas - Filho, Gilson Bras Broseghini (2019)
Once fructose consumption increased in the last decades, also increased the concerns about its effects upon the organism. It is already known that the chronic consumption of fructose induces metabolic disorder such as hyperglycemia and dyslipidemias, and these factors are strongly correlated with vascular disfunction. Due to fructose lipogenic potential, the high fructose diet was adopted by the scientific community as a model of metabolic dysfunction which allowed investigate how factors as hypertriglyceridemia and hyperglycemia are correlated to cardiovascular diseases. Thus, there is a need to determine whether fructose de per si has its own responsibility upon the vascular changes observed in this model, regardless of the metabolic scenario that it imposes. In order to verify if the vascular alterations observed during long-term fructose supplementation precede fructose-induced dyslipidemia, hyperglycemia, and insulin resistance; to establish the role of endothelium and perivascular adipose tissue in vascular modulation after fructose supplementation; and to assay whether the early vascular changes are sex dependent, we supplemented rats of both sexes for 4 days with 10% fructose solution via drinking water to assess vascular reactivity of aortas before the scenario of metabolic syndrome consolidated by prolonged use of fructose. Our data revealed that the consumption of fructose during 4 days promotes a reduction of vasoconstricting response to phenylephrine in aortas from female rats when without perivascular adipose tissue (rmax female CT = 116±2 Vs FR = 90±2*, %KCl, *=p<0,05 vs CT), despite do not chance it in aortas from male rats (rmax male CT = 85±3 Vs FR = 81±3, %KCl). We have also shown that the effects of fructose are different between male and female, recruiting the endothelium for fructose action upon the female aorta and the perivascular adipose tissue with regard to the reduction of vascular reactivity observed in males (rmax male+PVAT CT = 92±4 Vs FR = 69±5*, %KCl, *=p<0,05 vs CT). Moreover, males were more susceptible than females to the metabolic changes induced by fructose consumption, because although fasting glycemia was not altered in both sexes, insulin resistance and serum parameters such as VLDL VLDL (male CT = 19±3 vs FR = 37±7*, mg/dL, *=p<0,05 vs CT) and triglycerides (machos CT = 98±16 vs FR = 188±33*, mg/dL, *=p<0,05 vs CT) were higher in that group. The data determine that the consumption of fructose for 4 days alters the vasoconstrictor response to phenylephrine in aortas differently between sexes, recruiting endothelium for its action on female aorta and PVAT with respect to the reduction of vascular reactivity observed in males. The results obtained in the present study demonstrate the importance of these variables in relation to vascular alterations induced by fructose supplementation and stimulate new studies that will explore gender differences regarding vascular function changes, focusing on endothelial modulation and the participation of perivascular adipose tissue in fructose-induced vascular changes